Smokeless tobacco utilization among tribal communities in India: A population-based cross-sectional analysis of the Global Adult Tobacco Survey, 2016–2017 - Agrawal, Ritik; Ghosal, Shishirendu; Murmu, Jogesh; Sinha, Abhinav; Kaur, Harpreet; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Public Health, 2023)
Evidence on smokeless tobacco use is scarce among the indigenous communities with the available literature based either on a specific tribe or a particular region. We aimed to estimate the prevalence of smokeless tobacco, and assess its correlates among tribal communities in India. We utilized data from Global Adult Tobacco Survey-2 conducted in 2016-17. A total of 12,854 tribal people aged >15 years were included in this study. The utilization of smokeless tobacco was estimated using the weighted proportion and its correlates were assessed by multivariable logistic regression reported as adjusted odds ratio (AOR) with 95% confidence interval. The prevalence of smokeless tobacco use was 32%. Participants aged 31 to 45 years [AOR: 1.66 (1.37-2.00)], males [AOR: 2.37 (1.94-1.90)], daily wage/casual labourers [AOR: 5.32 (3.39-8.34)] were observed to have a significant association with smokeless tobacco. Willingness and attempt to quit smokeless tobacco were higher in Eastern India (31.2%) and central India (33.6%), respectively. We observed one third of the tribal individuals used smokeless tobacco in India. Tobacco control policies should prioritized males, rural residents, and individuals with fewer years of schooling. Culturally appropriate and linguistically tailored messages are required for behavioural change communication.